POTENSI EKONOMI SEKTORAL DAN KOMODITI UNGGULAN ‎DAERAH ‎PENYANGGA IKN (SAMARINDA, BALIKPAPAN, ‎PENAJAM PASER ‎UTARA, DAN KUTAI KARTANEGARA)‎ - Erni Setiawati; Siti Rohmah; Winda Dwi Cahyani; Lia Novi Nur Rahayu (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2025)
The economic potential and superior commodities of the region are interpreted as sectors and commodities that have high competitiveness. A sector is said to have great potential if it has a fairly high comparative advantage (advantage) compared to the same sector in other regions. The purpose of this study is to measure the comparative advantages of a sector, subsector, or superior commodity in the buffer area of the Nusantara IKN, namely Balikpapan, North Penajam Paser, Samarinda, and Kutai Kartanegara. The research method is quantitative descriptive. The data collection technique uses documentation studies with external data sources (secondary data), namely utilizing and collecting data from official documents or data that has been processed by other institutions or organizations, such as census data or economic data government reports, regional economic statistics agencies, or scientific publications. The data used are GDP data and the GDP growth rate or economic growth rate of each sector or subsector according to the business field for the period 2018–2022 in the IKN buffer area; Samarinda, Balikpapan, Penajam, and Tenggarong. The technical data analysis uses the Location Quotient (LQ) analysis method. LQ is used to find out how much specialization the base or leading sectors have. LQ analysis uses two analysis methods, namely static location quotient (SLQ) and dynamic location quotient (DLQ). The results of the study concluded that Samarinda City has 14 base/flagship economic sectors, where the financial services sector is the leading sector. Balikpapan City has 13 base/flagship economic sectors, with the leading sector being transportation and warehousing. North Penajam Paser Regency (PPU) has 9 base/flagship economic sectors; the Agriculture, Forestry, and Fisheries sectors are the leading sectors, while the lagging sectors are the Accommodation and Food and Beverage Provision Sector. Kutai Kartanegara Regency only has 2 base/flagship economic sectors as leading sectors, namely the Agriculture, Forestry, and Fisheries sector and the Mining and Quarrying sector, and the lagging sectors are the Electricity and Gas Procurement Sector and the Construction sector.